(untitled) (MAUSAM, 2004)
The prediction of fog remains a difficult problem due to its dependence on micro-physical meso-scale and synoptic scale processes. In this paper synoptic evaluation and sounding analyses of Delhi are made in relation to the occurrence of fog over the city and finally an objective method is evolved for the prediction of fog over Delhi applying statistical multiple discriminating analysis. The study shows that : (i) Moisture incursion from the Bay of Bengal by the prevailing easterlies in the boundary layers particularly, at 925 hPa and lower levels cold air advection by the northerlies to the west are the two synoptic scale features associated with the fog episode over Delhi in December 1999, (ii) Sounding analyses of Delhi ( December and January of 1997-2000 ) reveals that fog occurrence of Delhi are dominant when the wind speed (at 1000 hPa) does not exceed 5 knots, minimum temperature is less then 9° C, dew point depression (1000 hPa) is less then 6° C and dew point (1000 hPa) is greater than 6° C. Most of the fog occurrences are associated with the backing condition of wind between 1000 hPa and 700 hPa and (iii) The objective method developed with threshold values of these parameters at different ranges applying successive multiple discriminating analyses is found to be reasonably skillful.